Changes in dual energy X-ray absorptiometry parameters in postmenopausal women with osteoporosis who received at least 12 months of denosumab treatment: Effectiveness of denosumab treatment in postmenopausal osteoporosis - Kaysin, Meryem Yilmaz; Aktaş, İlknur and Özkan, Feyza Ünlü and Zeytin , İrem Buse Kurucu (Journal of Surgery and Medicine, 2022)
Background/Aim: Denosumab is a human monoclonal antibody that binds to the receptor-activated nuclear factor kappa beta ligand (RANKL). Densosumab leads to a reduction in bone resorption by inhibiting RANKL and has been approved for treating postmenopausal osteoporosis (OP). The present study investigated real life data by evaluating the demographic data of postmenopausal patients with OP who received denosumab treatment and the changes in dual energy x-ray absorptiometry (DEXA) parameters before and after denosumab treatment. Methods: This retrospective cohort study included 49 postmenopausal female patients followed in our OP outpatient clinic who were treated with 60 mg subcutaneous denosumab every six months for at least 12 months. The study retrospectively analyzed and recorded patient age, body mass index, age of menopause, fracture history, antiresorptive and/or anabolic drug treatment history, and pre- and post-denosumab T-scores in addition to L1–4, femoral neck, and total hip bone mineral densities (BMDs) on DEXA scans. The changes that occurred before and after the treatment in addition to those that occurred after the treatment based on whether previous anabolic or antiresorptive agents had been used were statistically compared. Results: The L1–4 and total hip T-scores and L1–4 and total hip BMD values measured prior to denosumab treatment showed a statistically significant increase after denosumab treatment (P < 0.001, P = 0.002, P = 0.028, and P = 0.002, respectively). No statistically significant changes in the femoral neck T-score and BMD after denosumab treatment compared to that before denosumab use (P = 0.056 and P = 0.138, respectively) were found. Furthermore, no statistically significant difference between the pre- and post-denosumab DEXA parameters in the patients who used antiresorptive agents and those who did not (P > 0.05) was found. Additionally, pre- and post-denosumab parameters were not statistically significantly different between those who received and did not receive anabolic therapy before denosumab (P > 0.05). Conclusion: Denosumab treatment for postmenopausal OP leads to a significant increase in lumbar and total hip T-scores and BMDs.